A framework for certification of large-scale component-based parallel computing systems in a cloud computing platform for HPC services - Dantas, A. O. (2017)
This paper addresses the verification of software components in the context of their orchestration to build cloud-based scientific applications with high performance computing requirements. In such a scenario, components are often supplied by different sources and their cooperation rely on assumptions of conformity with their published behavioral interfaces. Therefore, a faulty or ill-designed component, failing to obey to the envisaged behavioral requirements, may have dramatic consequences in practice. Certifier components, introduced in this paper, implement a verification as a service framework and are able to access the implementation of other components and verify their consistency with respect to a number of functional, safety and liveness requirements relevant to a specific application or a class of them. It is shown how certifier components can be smoothly integrated in HPC Shelf, a cloud-based platform for high performance computing in which different sorts of users can design, deploy and execute scientific applications.